Productive Waqf in Society 5.0: Islamic Law and Global Development - Widjiono Purnomo; Maher Zain Lillah; Yabit Lirobbihi; Litthoifin Wal Akifin (Walidem Institute and Publishing (WIP), 2025)
Objective: This study aims to analyze the role of productive waqf as an instrument of Islamic law in supporting global development within the context of Society 5.0. It explores how waqf can respond to contemporary socio-economic challenges through a sustainable and inclusive approach. Theoretical framework: The study integrates Islamic philanthropic theory and sustainable development concepts, positioning productive waqf as a socio-economic tool for promoting welfare, equity, and inclusive growth in modern society. Literature Review: Previous studies indicate that productive waqf has significant potential in enhancing social welfare, particularly in sectors such as education, healthcare, and micro-enterprises. Islamic economic law literature highlights waqf as a strategic philanthropic instrument, while sustainable development discourse recognizes its relevance in promoting equity and long-term socio-economic stability. However, existing research also identifies persistent challenges, including governance issues, lack of transparency, and regulatory fragmentation. Methods: This research employs a qualitative approach using a literature review method. Data are collected from academic publications, institutional reports, and policy documents related to productive waqf, Islamic law, and global development. The analysis focuses on conceptual understanding, regulatory frameworks, and implementation practices. Results: The findings reveal that productive waqf can play a vital role in advancing global development by fostering economic empowerment and social inclusion. Nevertheless, its effectiveness remains constrained by limited public awareness, weak institutional management, and inconsistent legal frameworks. Strengthening governance, improving regulatory integration, and enhancing transparency are essential to optimize its impact in the Society 5.0 era. Implications: This study is limited to secondary data and literature-based analysis. Future research is recommended to incorporate empirical approaches to validate the practical impact of productive waqf in different socio-economic contexts. Novelty: This study contributes to the literature by integrating Islamic law perspectives with global development discourse in the context of Society 5.0. It offers a comprehensive view of productive waqf as a sustainable instrument capable of addressing modern development challenges.